Formulation of Standard Operating Procedures for Tickets for Sumber Gempong Tourism Management - Friska Putri Aprilia; Chitra Laksmi Rithmaya (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
In the tourism industry, human resources play an important role in an organization's success. In achieving effective and efficient tourism management, namely through the implementation of standard operating procedures during operations. On the Sumber Gempong tour, several obstacles affect ticket sales, including inaccurate employee checks and deficiencies in visitor counting. This study aims to compile standard operating procedures in the implementation of employee work in ticket sales at the Sumber Gempong tourist spot. The preparation of process SOPs is important for organizing and carrying out tasks and processes within an organization. The method used in this research is a qualitative descriptive approach. Data obtained through observation techniques, interviews, and documentation. Researchers will make standard operating procedures in the form of steps or work processes in the ticket sales section. The results of this research will make it easier for employees to know their duties and responsibilities.